Influência de dinamizações de Cina para o controle de Meloidogyne incognita em tomateiro - Swarowsky, Rafael Augusto (2014)
Considering the importance of the tomato crop and the high costs of the control of Meloidogyne incognita with resistant cultivar or nematicides, grows the search of new alternatives to control the root-knot disease. The homeopathy may be an alternative way of control, by inducing resistance. This study aimed to evaluate the influence of the homeopathic drug Cina in the number of root galls, eggs and J2 present in the roots of tomato and soil, as well as the growth of tomato plants. The dynamizations used were 12, 24, 50, 100, 200, and 400CH (centesimal hahnemanian dilutions). It was also used the chemical carbofuran, 70% ethanol and water as control treatments. The assay was conducted in pots in greenhouse for the in vivo assay and in laboratory for the in vitro ones. In both assays, homeopathic treatments were diluted with distilled water to 0.1% before application. On the in vivo assay, the homeopathic drug was applied weekly by foliar spray. The first treatments were done three days before pathogen inoculation with approximately 5000 eggs and 500 J2 per pot. The evaluations were made 50 days after transplanting of the tomato seedlings and 44 days after inoculation. The Cina demonstrated effectiveness in stimulating root development, once the results of root volume were higher in homeopathic treatments than in control. Cina 100CH also favored the growth of the stalk diameter of the plants. However, the homeopathic product showed no nematostatic nor nematicide effect